Low Temperature Sintering of Gadolinium Doped Ceria Electrolyte - Goyal, Jahnvi (My University, 2023)
Gadolinium doped Ceria electrolytes has been considered as the most suitable materials for IT- SOFCs. In this study, the reduction in the sintering temperature has been done for the GDC doped samples. The effects of additions of Cu, Co and Bi oxide as sintering aids on Gd0.1Ce0.9O1.95 has been studied. Powders of Gadolinium Doped Ceria with varying ratios of sintering aids was prepared and converted into pellets. These pellets were then sintered at various temperatures to ensure densification. The sintered GDC pellets with varying ratios of sintering aids were characterized through XRD, SEM and Impedance analysis. Density measurements were done and 3 wt% ratio of sintering aids shows the highest density. The XRD patterns show no secondary phases, which suggests that a single phase is formed in each sample. Also, the crystallite size decreases with increase in sintering aid concentration. From SEM images it is observed that the grain size has decreased considerably with respect to initial GDC sample without doping and dense microstructure was observed for 3 wt% samples. From the impedance analysis, high conductivities were obtained for Cu and Co doped GDC samples but conductivity decreases for Bi doped GDC samples than pure sample without addition of sintering aid. The conductivity follows the order: Bi< Cu< Co.
Keywords: Gadolinium doped ceria; Sintering aids; Anode; Cathode; Electrolyte